Pemanfaatan Lahan Sempit dengan Sistem Vertikultur di Kelurahan Kalijudan, Kecamatan Mulyorejo Kota Surabaya - Achmad Firman Maulana; Moch. Maulana Kurnianda Saputra; Rizki Revashandi Ihsan Laduni (Lembaga Pengembangan Kinerja Dosen, 2024)
The small number of people cultivating horticultural crops, especially vegetables, means that people can only buy vegetables to meet their vegetable food needs, where the main factor for this is the decline in the area of productive land used as agricultural land and cultivation caused by the growth of population density in Indonesia. Therefore, the solution to the existing problem is to provide openness of insight and assistance in utilizing narrow land for plant cultivation. One way to cultivate plants is by using the vertical cultivation method. In implementing this activity, the aim is for Kalijudan residents to have knowledge about the vertical cultivation system and plastic bottle waste management. The implementation of this activity uses the method of socialization and training activities or direct practice. Where, the target audience in the practice of this activity is elementary school students and Kalijudan residents. From the results of the discussion, it was concluded that this activity is useful because it can introduce residents and change the condition of the Kalijudan sub-district which was originally a narrow land without plants into a narrow but green land. In addition, this vertical cultivation activity also has benefits in reducing plastic waste that accumulates in the Kalijudan environment.